Brachial plexus injury secondary to pseudoaneurysm of axillary artery after glenohumeral dislocation: case report - Douglas Ribas Schumann; Mauro José Superti; Felipe Candido Seyboth; Gabriella Eduarda Jacomel (Revista Brasileira de Ortopedia)
ABSTRACT Lesions of the axillary artery and consequent compression of the brachial plexus are extremely rare in patients with glenohumeral dislocation and may have greatly varying clinical manifestations. This joint is one of the most affected by dislocation in the human body, accounting for approximately 45% of cases. Less than 1% of patients with shoulder dislocation have vascular complications; however, when there is damage in the axillary artery, the incidence of associated brachial plexus injury is 27% to 44%. The authors report on a case of brachial plexus compression by an axillary artery pseudoaneurysm after a glenohumeral dislocation, aiming to highlight the existence of this association, in order to make an early diagnosis and avoid serious complications, such as neurologic injury.